'Enforcement of Patent Law in Civil Proceedings' – A Conference Report on the Fifth Bi-national Seminar of TU Dresden and Charles University in Prague, 26 November 2019. Issue 6 (30th April 2020) - Petrlík, David; Linke, David
Abstract: What is the law good for if it cannot be enforced? This question is currently virulent in patent law, especially when it comes to the enforcement of injunctive relief claims. From the German perspective, a question arises: does a patent infringement have to automatically result in an injunction (as is the situation currently according to Sec. 139 of the Patent Law Act) or should exceptions be made in special cases? In particular, the automotive industry and also the IT sector demand a modernisation of this provision by introducing a proportionality test, as even the smallest patentable components in networked products can lead to the entire production being blocked in the event of a successful injunction action. Similar problems exist in US patent law. The enforceability of Czech patent law also faces challenges that need to be solved. For this reason, the fifth seminar on the topic 'Enforcement of Patent Law in Civil Proceedings' took place on 26 November 2019 at Charles University Prague.